Bhabinkamtibmas Efforts in Preventing Radicalism in Cirebon Polresta - Arafat, Chakra Muhammad (Police Studies Review, 2024)
This study aims to analyze the role of Bhabinkamtibmas in preventing radicalism in Cirebon Police. This research uses a qualitative approach with a case study method. Data sources include 1) Kapolres, 2) Kasat Binmas, 3) Kasat Intelkam, and 4) Bhabinkamtibmas Cirebon Police. Data analysis was performed by data reduction, data display, and conclusion drawing. The results of the study show that 1) The role of Bhabinkamtibmas in preventing radicalism in Cirebon Police has referred to Article 16 of the Head of Indonesian Police Regulations No. 3 of 2015 concerning Community Policing. Bhabinkamtibmas in preventing radicalism in Cirebon Police promotes Door to Door System activities to people's homes. Bhabinkamtibmas in the prevention of radicalism in Cirebon Police strives to guide the implementation guide of the Bhabinkamtibmas task, namely the Smart Book of Bhabinkamtibmas .; 2) Factors which hamper the role of Bhabinkamtibmas in preventing radicalism in Cirebon Police can be grouped into internal factors and external factors. Internal factors, are factors that cause within the National Police organization, namely the problem of human resources (number of members, level of education, skills or abilities of members, and insight about radicalism), facilities and infrastructure, and member motivation. External factors, are factors that cause external police organizations, namely community culture, non-functioning FKPM, lack of understanding of the community with the concept of Community Policing, and a sense of community awareness of the surrounding environment that is still low and tends to be indifferent; 3) Efforts made by the Cirebon Police in overcoming obstacles related to the implementation of the role of Bhabinkamtibmas in preventing radicalism, include through the support of cyber patrol in the Criminal Unit of Criminal Investigation and optimizing Polmas.